Management of Erysiphe pisi through strobilurin and EBI fungicides - AMIT KUMAR, S.K. GUPTA* and (Indian Phytopathology, 2008)
Various fungicides were evaluated for the control of powdery mildew (Erysiphe pisi DC.) of pea in protective and eradicative spray programmes. Carbendazim caused complete conidial germination inhibition followed by wettable sulphur and kresoxim methyl while hexaconazole was least effective under in vitro conditions. Difenoconazole (10 Âµg/ml) caused >50 per cent inhibition of germtube elongation besides affecting the morphology of germtubes which appeared distorted. In protective spray programme, three sprays of kresoxim methyl (0.1%) at fortnightly intervals were found highly effective followed by difenoconazole, penconazole, diniconazole and hexaconazole while wettable sulphur was least effective. Maximum postsymptom antisporulant activity of 10 days was provided by kresoxim methyl (0.1%) and hexaconazole (0.05%), which can be utilized in planning various spray programmes.